Análise "in vitro" da resistência adesiva de sistemas adesivos autocondicionantes com o substrato dentinário após a desproteinização dentinária - Antury, José David Ruan (2005)
The purpose of this study was to evaluate “in vitro” the bond strength of the self etch adhesive systems One Coat SE Bond, Self Etch Bond, and XENO®III with the dentin substrate, by means of the microtensile bond strength test, after dentin deproteinization. The conventional adhesive system Adper Single Bond™/3M™-ESPE™ was used as group control. Thirty five human integral third molars were chosen. Theirs occlusal surfaces were cut 3mm±1mm. The dentin surfaces polished with silicon carbide sandpaper of granulation 600 during 1min, in a Politriz. Each group (n=5) received its respective adhesive systems, GI: controle (hybrid layer); GII, GIV and GVI: self etch adhesive systems (reaction-integration); GIII, GV and GVII: self etch adhesive systems (deproteinization). The teeth were restored with resin composite Filtek Z-250 3M™/ESPE™. 24 hours after, the teeth were sectioned using a diamond saw mounted in a Labcut 1010 machine, to get perpendicular sections to the bonding interface with a cross-sectional area to the approximately 0,7 mm2. Were selected 3 specimens per group. Which were prepared and analyzed through the scanning electronic microscope of camp emission and the “confocal laser scanning microscope”, the remaining specimens were submitted to microtensile bond strength in an universal testing machine, at a crosshead speed of 1 mm/min. the mode of fracture was observed using a optic microscope. For each one of the self etching adhesive systems a viscosity test was accomplished. The values of bond strength were submitted to statistical analysis using the Kruskal-Wallis test. The results had shown that the self etch adhesive system XENO®III, after the deproteinization with NaOCl 5,2% (43,60±11,44 MPa) presented the higher values of bond strength. The lowest values were observed in the self etch adhesive system One Coat SE Bond with and without deproteinization (27,50±8,75 MPa) and (27,07±7,27 MPa) respectively. The Self Etch Bond with NaOCl 5,2% demonstrated higher values of bond strength. The microscopy analyses allowed to observed the differences between the adhesive interfaces gotten (hybrid layer, reaction-integration, deproteinization). By this study was possible demonstrated that the dentin deproteinization through the application of NaOCl 5,2%, not influenced on the bond strength of the self etch adhesive systems One Coat SE Bond and XENO®III. In the self etch adhesive system Self Etch Bond with NaOCl the bond strength increased significantly.